1980
DOI: 10.1007/bf00037252
|View full text |Cite
|
Sign up to set email alerts
|

Autotetraploidy in caraway (Carum carvi L.) for the increase of the aetheric oil content of the seed

Abstract: An autotetraploid population of caraway (Carurn carvi L.) was produced by treating the growing points of young plants with a 0.2% colchicine solution. Selection on morphology, pollen size and pollen shape, followed by a selection on seed size proved to be an effective way to identify the mixoploid C, plants. Three percent of the treated plants produced a tetraploid progeny. Moderate selection in the C, and the C, population resulted in an improvement of the average seed-set to the amount of 50% of the diploid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…The plant caraway plant has been shown to have stomachic, antispasmodic, antibacterial, antifungal, antiulcerogenic, and antiproliferative properties and can be an effective insect repellent (Peirce, 1999;Eddouks et al, 2004;Deeptha et al, 2006). The extract of caraway mainly contains ethereal (essential) oil, aromatic ketone, carvone, D-limonene, fatty oil, protein compounds, waxes, tanning agents, resins, flavonoids, organic acids, coumarin compounds, minerals, and other salts (Dijkstra & Speckmann, 1980;Weiss, 2002;Dyduch et al, 2006;Agnieszka et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The plant caraway plant has been shown to have stomachic, antispasmodic, antibacterial, antifungal, antiulcerogenic, and antiproliferative properties and can be an effective insect repellent (Peirce, 1999;Eddouks et al, 2004;Deeptha et al, 2006). The extract of caraway mainly contains ethereal (essential) oil, aromatic ketone, carvone, D-limonene, fatty oil, protein compounds, waxes, tanning agents, resins, flavonoids, organic acids, coumarin compounds, minerals, and other salts (Dijkstra & Speckmann, 1980;Weiss, 2002;Dyduch et al, 2006;Agnieszka et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In Fenugreek (Trigonella foenum-graecum L.) the application of trifluralin in 22.5 ”M concentration at 24 h had the most ploidy induction and the karyotypes of chromosomes changed (Afshari et al, 2009). a finding also reported in Tanacetum parthenium (Saharkhiz, 2007), Mentha mozaffarianii (Ghani et al, 2014), Catharanthus roseus (Hoseini et al, 2012), Dracocephalum moldavica (Omidbaigi et al, 2010), Ocimum basilicum (Omidbaigi et al, 2012) and Carum carvi L. (Dijkstra & Speckmann, 1980).…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies on tetraploid varieties of feverfew (Tanacetum parthenium L.) (Saharkhiz, 2007), caraway (Carum Carvi L.) (Dijkstra & Speckmann, 1980) and rosy periwinkle (Catharanthus roseus (L.) G.Don) (Hoseini et al, 2012) have shown a reduction in growth rate in the early stages of growth along with a reduction in plant height during the flowering stage as compared with their diploid counterparts. Indeed, a common outcome of polyploidy in plants is a reduction in the number of cell divisions in the early stages of growth (te Beest et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Delayed flowering and seed maturation which was also found for tetraploid caraway (DIJKSTRA & SPECKMANN, 1980), could help in identifying the tetraploid plants. Therefore, the most reliable method for identifying polyploid plants was by cytological examination of the PMC's.…”
Section: Discussionmentioning
confidence: 86%